BUSINESS MODEL VALIDATION OF MICRO BUSINESS IN READY-TO-WEAR CLOTHING INDUSTRY (CASE STUDY: AULEEA.OS IN SURABAYA CITY) - Astri Ghina; Luvita Puteri Jamilah (Jurnal Ekonomi, 2023)
Microbusiness has evolved into one of the key areas for Indonesia's economic expansion, including the ready-to-wear clothing industry. The large number of ready-to-wear clothing industries has created intense competition, driving them to innovate their products. This research focuses on testing the prioritized elements of the business model. The validation of this business model is conducted to develop the product of the microbusiness Auleea.os, which operates in the ready-to-wear clothing sector. A qualitative case study research approach is used as the research strategy. Interviews and observations will be employed as data collection techniques for the study. To validate the relevant values, information obtained from interviews and observations will be analyzed through business idea testing. This analysis will be utilized to provide recommendations and further actions in the development of Auleea.os microbusiness. The main validation process will be conducted on the prioritized business model hypotheses, which are identified by their high impact and lack of supporting evidence. The research findings indicate that the new business model ideas used by Auleea.os have been validated and can meet the needs and desires of potential consumers. In subsequent similar research, this study is expected to serve as a reference guide. The findings from this analysis are used to provide input in the production of Auleea.os business products.